1997
DOI: 10.1143/jjap.36.5163
|View full text |Cite
|
Sign up to set email alerts
|

Percolation Threshold of Carbon Black-Polyethylene Composites

Abstract: We extend our previous formulation of low-energy QCD in terms of an effective lagrangean containing operators of dimensionality d ≤ 6 constructed with pseudoscalars and quark fields, describing physics below the scale of chiral symmetry breaking. We include in this paper the vector and axial-vector channels. We follow closely the Extended Chiral Quark Model approach and consistently work in the large-N c and leading log approximation and take into account the constraints from chiral symmetry and chiral symmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 11 publications
3
47
0
Order By: Relevance
“…Below Pt, the AC conductivity of carbon blackfilled polyethylene matrix composites becomes AC loss current in proportion to frequency. [7] Near Pt, apart from the loss current in proportion to the frequency, frequency does not have any impact. Also, different current elements depending on electric fields are repeated.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Below Pt, the AC conductivity of carbon blackfilled polyethylene matrix composites becomes AC loss current in proportion to frequency. [7] Near Pt, apart from the loss current in proportion to the frequency, frequency does not have any impact. Also, different current elements depending on electric fields are repeated.…”
Section: Resultsmentioning
confidence: 92%
“…[6] This is identical to the result of Nakamura. [7] Nakamura mentioned the need to review the change behavior of relative dielectric constant in relation to the amount of filled black carbon in association with effective medium approximation theory (EMA theory) as the size of carbon black clusters tends to remain limited when the amount is below Pt. [6,8] investigate the effect of temperature on the dielectric properties of carbon black-filled polyethylene matrix composites below the Pt based on the EMA theory.…”
Section: Introductionmentioning
confidence: 99%
“…The volume filler fraction of SiN10 is 3 % (assuming a filler density of 3.44 g/cm 3 and a polymer density of 0.95 g/cm 3 ), which is well below the threshold for percolation for conducting spheres in a non-conducting matrix [28]. However, numerical modelling calculations by other authors [15] have shown that it is possible to obtain a percolating network in such a system by introducing water shells of ~60 nm thickness around each nanoparticle.…”
Section: F Simulation Of Percolationmentioning
confidence: 98%
“…In the silica nanocomposites, a percolating network is not formed, due most likely, to particle aggregation (see Fig. 3); aggregation allows water shells locally to overlap so reducing the overall volume fraction of the system occupied by water-containing interphase regions to below that required for percolation [15,28].…”
Section: F Simulation Of Percolationmentioning
confidence: 99%
“…From the experimental and theoretical investigations, it is reported that the drastic variation of conductivity and permittivity takes place around the φ c . 13,14 Since we used the same Permalloy particles in the preparation of heat-treated and non-treated particle composites, the critical particle content of the mechanical percolation must be the same in the two particle conditions. Therefore, it is considered that the critical particle content φ c in the electrical percolation was increased by the decrease of the electrical conductivity due to the heat-treatment of particles.…”
Section: Resultsmentioning
confidence: 99%